2019
DOI: 10.2478/sab-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Some Tobacco (Nicotiana Tabacum L.) Genotypes by Morphological Traits

Abstract: Simple lattice design with two replicates was used to evaluate 25 tobacco genotypes. The following eight traits were measured and evaluated: plant height (PH), leaf length (LL), leaf width (LW), leaf number per plant (LN), stem girth (SG), leaf area (LA), dry leaf yield (DLW), and fresh leaf yield (FLW). The genotype by trait biplot for tobacco dataset explained 73% of the total variation of the standardized data. The polygon view of genotype by trait presented for the eight different traits of tobacco genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…They identified genotypes which could be used as parents in future breeding programs. Porkabiri et al (2019) carried out a morphological characterization study with 25 tobacco genotypes, and reported that leaf width and length parameters were the major determinants of ideal genotype with the highest yield. These results indicate that characterization of various genetic resources could help in widening the genetic basis for plant breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…They identified genotypes which could be used as parents in future breeding programs. Porkabiri et al (2019) carried out a morphological characterization study with 25 tobacco genotypes, and reported that leaf width and length parameters were the major determinants of ideal genotype with the highest yield. These results indicate that characterization of various genetic resources could help in widening the genetic basis for plant breeding programs.…”
Section: Introductionmentioning
confidence: 99%